Grain dust for finishing cattle - D. Axe; H. Ilg; K. Bolsen; Keith C. Behnke (Kansas Agricultural Experiment Station Research Reports, 1980)
Two finishing trials with heifers and steers were conducted to determine the value of grain dust (GD) to replace cracked corn and to compare soybean meal and urea as protein supplements. Results of the 104-day heifer trial showed that 50% GD supported the least efficient gains. Heifers fed 0 and 25% GD rations had similar performances. In the 75-day steer trial, replacing 12.5 or 25% of the cracked corn in the ration with GD did not affect rate of gain. However, steers fed the GD rations consumed more feed and were less efficient than steers fed the cracked corn, control ration. In both trials, soybean meal and urea supplements gave similar rates and efficiencies of gain.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Grain dust; Finishing cattle; Soybean meal